1925
DOI: 10.1084/jem.42.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Bacterium Lepisepticum

Abstract: Inorganic iron substances of known chemical structure have been tested for their ability to function as the X factor in the growth of bacteria of the hemophilic, anaerobic) and hemorrhagic septicemia groups. Each iron compound possessing this biocatalytic activity showed oxygen-absorbing and peroxidase properties. The interrelation of these mechanisms is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1926
1926
1937
1937

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…De Kruif noted that "D" strains, inoculated into broth or peptone solutions, gave rise to "G" variant forms after 48 to 72 hours incubation (2). Later, we made a more detailed study of the growth of this type (14,15), and noted the following facts: (1) that "D" strains, inoculated into aerobic meat infusion broth, pH 7.4, in quantifies less than 100,000 per cc., did not live; (2) that larger seedings multiplied after a period of lag, until a maximum number of 1,000,000,000 per cc. was reached; (3) that after 48 to 72 hours incubation, "G" variants appeared in increasing numbers, until they replaced entirely the original "D" forms.…”
Section: Growth Requirements and Characteristicsmentioning
confidence: 92%
“…De Kruif noted that "D" strains, inoculated into broth or peptone solutions, gave rise to "G" variant forms after 48 to 72 hours incubation (2). Later, we made a more detailed study of the growth of this type (14,15), and noted the following facts: (1) that "D" strains, inoculated into aerobic meat infusion broth, pH 7.4, in quantifies less than 100,000 per cc., did not live; (2) that larger seedings multiplied after a period of lag, until a maximum number of 1,000,000,000 per cc. was reached; (3) that after 48 to 72 hours incubation, "G" variants appeared in increasing numbers, until they replaced entirely the original "D" forms.…”
Section: Growth Requirements and Characteristicsmentioning
confidence: 92%
“…The extensive experiments of Webster and Baudisch (79) showed that aquo salt diluted to 0.01 mg. per cubic centimeter can replace the X factor with hemophilic bacteria. Influenza bacilli also grew in the presence of aquo salt, as did B. welcjiii and B. sporogenes.…”
Section: Cl2mentioning
confidence: 99%